Correlated Changes Between Volcanic Structures and Magma Composition in the Faial Volcanic System, Azores - Romer, René H. W.; Beier, Christoph; Haase, Karsten M.; Hübscher, Christian (Frontiers in Earth Science, 2018)
The interaction between magmatic and tectonic processes in ocean intraplate volcanism yields insights into the ascent and transport of magmas. Many oceanic intraplate studies lack a temporal component and do not consider changes in tectonic regime and/or magmatic processes during the evolution of magmatic systems. The eastern part of the Azores archipelago formed under the influence of both an intraplate melting anomaly and a system of ultraslow spreading rift axes. The majority of recent submarine and subaerial eruptions in the Azores occur along volcanic rift zones and thus melt transport and volcanic processes are largely controlled by tectonic processes, and are therefore ideally suited to study volcano-tectonic interactions. Here, we investigate how variable the magmatic and tectonic processes are in space and time and how they interact. We present new bathymetric, geophysical, geochemical and Sr-Nd-Pb isotope data from Faial Island and the surrounding seafloor, providing insights into the interaction between the asthenospheric melting anomaly and extensional lithospheric stresses. The bathymetry reveals large submarine volcanic rift zones on the western flank of Faial, including that of the 1957-1958 Capelinhos eruption. Based on absolute ages and seismic imagery, we develop a relative chronology of the magmatic evolution of the submarine rift zones. Their preferred WNW-ESE orientation implies that the stress field has not changed within the last 1 Ma. We can however show that melt productivity progressively decreased with time. Compositionally different magma batches fed distinct volcanic rift zones and edifices, suggesting that changes in the melting regime occur on a small spatial scale and that the distribution of compositionally similar lavas is tectonically controlled. As melt supply decreases, the tectonic influence on volcanism increases with a stronger localisation of melts along tectonically controlled lineaments. The youngest mafic and intermediate melts (<10 ka) on Faial are exclusively erupted along single rift zones and cover a smaller area, whereas the older volcanism was more widespread.